E-Wallet dan Perilaku Konsumsi Islam - Meyta Amelia Rusbianti; Clarashinta Canggih (Jurnal Ilmiah Ekonomi Islam, 2023)
Transaction systems in the form of non-cash payments using e-wallets offer many advantages and conveniences. The existence of these conveniences causes people to use their money to consume goods that are not in accordance with their needs, which is not in accordance with the principles of Islamic consumption. This study aims to examine the effect of using e-wallets on Islamic consumption behavior in the people of Surabaya. This research is quantitative with a causal associative approach, and uses a purposive sampling method to get 100 respondents who meet the research criteria. Data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS analysis tool. Research results show that the use of e-wallets is influenced by perceived trust. Meanwhile, perceptions of convenience, benefits, risks and security of using e-wallets have no impact on Islamic consumption behavior.